The Anomalous Left Brachiocephalic Vein in Adults - Yoo, Hyun Woo; Kim, Young Tong (Journal of the Korean Society of Radiology, 2019)
Purpose To classify anomalous left brachiocephalic vein (LBCV) in adult without cardiac anomaly, and evaluate CT findings of anomalous LBCV. Materials and Methods This study included 32 patients who were diagnosed anomalous LBCV using MDCT between March 2005 and August 2016. Subaortic LBCV divided into group I (with normal LBCV) and group II (without normal LBCV). We evaluated age, sex, diameters and diameter ratios of superior vena cava (SVC) and subaortic LBCV, the entering sites to SVC of subaortic LBCV and the azygos vein, and vascular tortuosity of subaortic LBCV. Results There were included 29 subaortic LBCV and 3 retroesophageal LBCV. There were not statistically significant in age, sex, diameter of SVC between subaortic groups (p > 0.05). The diameters of subaortic LBCV were thinner in group I. Diameter ratios of subaortic LBCV were lower in group I. The entering site of subaortic LBCV was higher than azygos vein in group I (64%) and same as azygos vein in group II (67%). Vascular tortuosity of subaortic LBCV was in 7 cases of group I. Conclusion It is important for radiologists to be familiar with CT findings of anomalous LBCV, since the radiologists give information of uncommon or rare anomalous LBCV to clinician.